Efficacy of secukinumab in an adolescent with generalized pustular psoriasis. - Karaca Ural, Z. (European Journal of Pediatric Dermatology, 2024)
Treatment protocols in generalized pustular psoriasis have not been clearly defined because it is a rare type of psoriasis. In the pediatric age group, the data are even less. Our knowledge about the use of biological agents is increasing day by day. Sekukinumab appears to be an effective agent in the rapid and complete remission of psoriasis.